The Effect Of Perception Of Trust, Perception Of Ease Of Use, Perception Of Benefits, Perception Of Risk And Perception Of Service Quality On Interest In Using Mobile Banking Bank Independent In Bekasi City - Okky Natalia; Rini Tesniwati (Publisher Cv. Inara, 2021)
The purpose of this study was to explain and analyze the effect of perceived trust, perceived convenience, perceived risk, perceived service quality on interest in using mobile banking at Bank Mandiri in Bekasi city. The research methodology used is a quantitative approach. The sample used is the customer of Bank Mandiri Bekasi City as many as 100 respondents. The data collection instrument used primary data. Primary data was obtained by using a questionnaire. Analysis of the data used in this study is multiple linear regression test, classical assumption test, autocorrelation test, multicollinearity test, heteroscedasticity test, determinant test, t test and f test with the help of SPSS version 24. The results showed that partially or simultaneously the perception of trust, perception of convenience, perception of risk, perception of service quality have a significant effect on interest in using bank Mandiri mobile banking in the city of Bekasi